ICTs for Improving Patients Rehabilitation Research Techniques : Second International Workshop, REHAB 2014, Oldenburg, Germany, May 20-23, 2014, revised selected papers /: Second International Workshop, REHAB 2014, Oldenburg, Germany, May 20-23, 2014, revised selected papers. (2015) - Unknown
No abstract available